Effect of temperature and air speed of drying pituca (Colocasia esculenta) sheets on flour quality - Sempertegui Silva, Jhon Andy (2024)
The impact of temperature and air velocity on the drying of pituca (Colocasia esculenta) sheets was investigated. The samples, 1.5 mm thick, were subjected to a tray dryer at three temperatures (45, 50 and 55 °C) and three air velocities (2.5; 3.0 and 3.5 m/s). After grinding the dried sheets, the physicochemical, microbiological and sensory properties of the pituca flour were analyzed. The findings indicated that the drying curves conformed to the exponential model proposed by Herdenson and Pabis, with a coefficient of determination greater than 96%. The optimum treatment, T9, used a temperature of 55 °C and a speed of 3.5 m/s. It showed a critical moisture of 1.53 g/g dry pituca, an equilibrium moisture of 0.9 g/g dry pituca, and a critical time of 20 minutes. Values for ash, moisture, mesophilic aerobes, molds and yeasts were recorded at 3.37%, 8.04%, 9.90x103 CFU/g, and 2.40x103 CFU/g respectively, with absence of Escherichia coli. At higher temperatures and air velocities, the best sensory ratings were obtained. In conclusion, these parameters result in superior quality for pituca flour in kinetic, physicochemical and sensory terms.